A Cross-Sectional Study of Association Between Socioeconomic Status and Maternal-Neonatal Bonding in Hospital-Based Care: Research Article (Journal of Pharma Insights and Research, 2025)
Neonatal health during the first 28 days of life remains a critical concern in global healthcare. This study investigated the relationship between maternal-neonatal bonding and various factors affecting neonatal outcomes in a tertiary care hospital in Rajahmundry, India. A cross-sectional study was conducted on 380 postpartum mothers between October 2023 and May 2024. Data collection involved direct interviews and medical record reviews, focusing on maternal demographics, socioeconomic status, clinical parameters, and care practices. The mean maternal age was 24 years (SD=5.2), with gestational numbers ranging from 1-4 (mean=2.1, SD=0.8). The study revealed that 38.9% of neonates required NICU admission, primarily due to infection, jaundice, and respiratory issues. Significant associations were found between NICU admissions and antenatal care (ANC) visits (p=0.037), with mothers having fewer than two ANC visits showing higher NICU admission rates. Socioeconomic status significantly influenced maternal-neonatal bonding (p=0.047), with 65% of mothers belonging to lower socioeconomic groups showing reduced awareness of essential care practices. Knowledge of Kangaroo Mother Care (KMC) and breastfeeding techniques was notably lower among mothers from lower socioeconomic backgrounds and those with fewer ANC visits. Additionally, maternal postpartum depression showed a notable impact on bonding quality.